2014
DOI: 10.1051/epjconf/20147700004
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Joint Research Project «Quantum Ampere» for the realisation of the new SI ampere

Abstract: Abstract.The metrology community lately has adopted the long-term aim of basing the SI unit system on fundamental constants of nature. The base electrical unit, the ampere, will then be re-defined in terms of a fixed value of the elementary charge e. The most direct realization of the new ampere definition requires controlling the number of electrons which flow in a unit time interval, and of counting the errors occurring in this process of clocking single electrons. State of the art nanofabrication technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Up to now, only one rather complicated setup was reported that achieved 1 µA/A accuracy [1]. To improve this situation, PTB is pursuing the development of a new picoammeter: the "Ultrastable Lownoise Current Amplifier" (ULCA) is a fully non-cryogenic single-box instrument based on specially designed op-amps and resistor networks, working as current-to-voltage converter [10], [11]. For the experiments reported here, a first prototype with an effective transresistance A tr = U out / I in of 50 MΩ with a temperature coefficient of 1.8 µΩ/Ω per Kelvin was used.…”
Section: Background and Methodsmentioning
confidence: 99%
“…Up to now, only one rather complicated setup was reported that achieved 1 µA/A accuracy [1]. To improve this situation, PTB is pursuing the development of a new picoammeter: the "Ultrastable Lownoise Current Amplifier" (ULCA) is a fully non-cryogenic single-box instrument based on specially designed op-amps and resistor networks, working as current-to-voltage converter [10], [11]. For the experiments reported here, a first prototype with an effective transresistance A tr = U out / I in of 50 MΩ with a temperature coefficient of 1.8 µΩ/Ω per Kelvin was used.…”
Section: Background and Methodsmentioning
confidence: 99%